Implicações socioambientais dos estudos ambientais (ras) utilizados no licenciamento ambiental de parques eólicos no Ceará - Brasil - Souza, Wallason Farias de (2020)
The generation of electricity by wind power in Brazil has grown considerably in the last two decades (2000-2020), going from an almost zero installed power to an installed power of 15.72 GW, representing 9% of the Brazilian electric matrix. The State of Ceará is the third in Brazil in installed power, with 2.11 GW, which corresponds to 47.8% of the installed power in the State, which is 4.49 GW (August 2020). The 2001 energy crisis (blackout) and the need to diversify the country's electrical matrix led to efforts by the public authorities to make better use of the potential of some regions of the country for the production of electricity from wind sources, among these regions, the coast of Ceará stands out. This research aimed to analyze the speeches of the Simplified Environmental Reports (RAS) of wind energy enterprises on the coast of Ceará (all available at SEMACE), aiming to identify whether the wind farms would represent a case of green grabbing (appropriation of land and resources) on the coast of Ceará. A qualitative data analysis program (ATLAS.ti) was used to encode and analyze green grabbing discourse in 18 RAS, totaling 4,200 pages, and field visits were made to the installed parks in search of material evidence of appropriation. The results found in the RAS discursive marks of “green grabbing” with the appropriation of land and resources based on environmental justifications and purposes in the implementation of wind farms in the coastal zone of Ceará, environmental studies with weaknesses and a high level of repetition of content and evidence of material appropriation in installed wind farms. The RAS presented themselves as fragile instruments for assessing environmental feasibility for wind farms in the coastal zone of Ceará, using the rhetoric of green grabbing to justify and minimize the socio-environmental impacts and the appropriation of land and resources.